Impact of management accounting reform in the public sector: The Portuguese case - Liberato, M. I.; Paiva, I. C. de S.; Serrasqueiro, R. (Journal of Accounting and Organizational Change)
Purpose Based on the New Public Management Theory and New Public Financial Management (NPFM) into the theoretical framework, this study aims to analyze the impact of implementing management accounting reform in the Central Public Administration in Portugal and how this implementation affects control, transparency and management reports within these organizations. Design/methodology/approach The research methodology is based on a questionnaire sent to all central public administration institutions in Portugal. The data were analyzed using a structural equation model, using the partial least squares tool. Findings The main findings, consistent with the NPFM, indicate that implementing the management accounting reform has a significant positive effect on increasing the quality of management reports and the transparency of public administrations, as well as contributing positively to the increase of control in these organizations. Thus, it can be concluded that managers of organizations perceive that the intended objectives of the accounting reform are being achieved. Research limitations/implications The study has some limitations, as the data are limited to central public administration, leaving the impact on local and regional administration unstudied. Practical implications This study helps public institutions understand the advantages of implementing management accounting because their managers need information for decision-making. This includes aspects such as control, enhancing organizational efficiency and effectiveness, improving transparency in public spending, and elevating the quality of reporting by considering reliability, timeliness and comparability. Social implications This study enhances citizens’ comprehension of management accounting in the Portuguese public sector, highlighting its role in improving control, transparency and management reports. It fosters increased interaction between society and government, ensuring that decisions align better with society’s needs. Originality/value The accounting reform in public administration is still ongoing in Portugal and is a unique opportunity to study the implementation of the reform in the area of management accounting with the heads of the organizations responsible for this task. This study allows us to know their perceptions regarding the impact that the implementation of the management accounting reform has on control, transparency and management reporting. This study also incorporates NPFM into the theoretical framework for a more comprehensive analysis of public sector accounting reforms.